PENGARUH TINGKAT INFLASI, PERTUMBUHAN EKONOMI, NILAI TUKAR RUPIAH DAN PENGUSAHA KENA PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI PADA DJP JAWA TIMUR III - Hany Ayu Rahma Maulidya; Maslichah Maslichah; Abdul Wahid Mahsuni (Universitas Islam Malang, 2021)
The purpose of this study is to analyze the effect of the inflation rate, to analyze the effect of economic growth, to analyze the effect of the rupiah exchange rate, to analyze the effect of the number of taxable entrepreneurs, and to analyze the effect of inflation rate, economic growth, rupiah exchange rate, number of taxable entrepreneurs on the value growth tax revenue at the Regional Office of DJP East Java III. The sample in this study uses a saturated sample determination technique that uses all members of the population to be used as a sample. This research data is in the form of a time series in the period 2017-2019 with monthly data, so the number of samples is 36 observations. The analytical methods of this research are Multiple Linear Regression Analysis, Descriptive Statistics, Normality Test, and Classical Assumption Test. The results of the study indicate that the rate of inflation, economic growth, Rupiah exchange rate and the number of taxable entrepreneurs simultaneously have an effect on Value Added Tax Revenue. Inflation Rate, Economic Growth, Rupiah Exchange Rate partially have no effect on Value Added Tax Revenue. The number of Taxable Entrepreneurs partially has a significant negative effect on Value Added Tax Revenue.Keywords: inflation rate, economic growth, rupiah exchange rate, taxable entrepreneur, and value added tax revenu.